Kluang cooperation loan application - Norfaezah, Noordin (2010)
Currently, Kluang Cooperation Society still has manual system using log book to manage and apply loan. Kluang Cooperative Society does not have any system to manage and record all data that related and to apply the loan. In manually, all the information about members and activities is on the log book or paper sheet. The applicant also must fill up the loan form using handwriting. This situation makes the staff of Kluang Cooperation difficult to find the information in the file at the rack in shortest time. So, the new system will develop due to this situation that performs the online function for registration as member, apply the three types of loans; personal loan, emergency loan and road tax loan, check loan's status, view loan record and print agreement meanwhile the admin can approve or reject loan status, search member and loan detail and generate loan. Kluang Cooperation Loan Application (KCLA) help and make easier to all member of Kluang Cooperation in the management of applying loan and also very suitable for the member of this cooperation to apply the loan in everywhere via online application.